Tata Kelola Urusan Pemerintahan Desa: Antara Harapan dan Realita (Studi di Desa Kuwolu dan Pandanajeng Kabupaten Malang) - Wanusmawatie, Ike; Fatimah Durrety, Shinta; Prasetyo, Elshaddai Hosanna; Sriyono, Muhammad Edo Edi (Jurnal Ilmiah Administrasi Publik, 2025)
This study aims to describe and analyze the governance of village government affairs in Kuwolu and Pandanajeng Villages, Malang Regency. The concepts of Governance, Local Government, and Public Services are used in this study. The method employed is qualitative with interactive analysis. The results indicate that in decision-making processes regarding government affairs impacting basic needs, infrastructure, and village community empowerment, the regional government dominates, while the community and village government act as supporters. Furthermore, transparency and accountability tend to be administrative, demonstrated more to higher levels of government rather than to the affected village communities. This occurs because the Village Government has stronger compliance towards the regional and central government as task assigners rather than towards the village community. This condition influenced by the pseudo-government status and structure of the village administration. In conclusion, the governance of village government affairs is currently in transition and can be optimally implemented if the status and structure of the village government change to a small local autonomous.